THE CATALAN CRISIS: SCENARIOS OF SOLUTION - Sheketa , Mariana; Stetsyuk , Natalia (Collection of scientific papers «ΛΌГOΣ», 2022)
Public opinion about the future of an independent Catalonia may be very ambiguous. One of the most controversial topics was the economic issue. On the one hand, Catalonia will manage its own national resources. However, other experts do not rule out the negative development of events for the Catalan economy when it decides to separate.